Explanation:
the exponential growth function is
f(t) = v0 × (1 + k)^t
1977 to 1989 is 12 years (t).
a)
so, we have
467 = 209 × (1 + k)¹²
467/209 = (1 + k)¹²
12th root(467/209) = 1 + k = 1.069295033...
k = 0.069295033...
b)
f(t) = 209 × 1.069295033...^t
c)
2009 = 32 years after 1977
f(32) = 209 × 1.069295033...³² = $1,783.478472... ≈
≈ $1,783.48
d)
double the value of 209 is 418.
418 = 209 × 1.069295033...^t
2 = 1.069295033...^t
t = log1.069295033...(2) =
= log(2)/log(1.069295033...) = 10.34554457... ≈
≈ 10.3 years
e)
2221 = 209 × 1.069295033...^t
2221/209 = 1.069295033...^t
t = log1.069295033...(2221/209) =
= log(2221/209)/log(1.069295033...) =
= 35.27452616... years ≈
≈ 35.3 years
35 years would mean end of 2012. so, 35.3 years would be early 2013.